Gamificação: uso de estratégias de ensino/aprendizagem na educação de pessoas surdas - Brito, Celso Carmelindo de (Brasil, 2024)
Gamification in the education of deaf people is an innovative approach that uses game elements to engage and motivate deaf students in their learning process. By integrating games, challenges and rewards into the educational curriculum, gamification makes learning more interactive, fun and effective for this audience. This study aims to investigate how gamification can be effective in the education of deaf people, with the aim of increasing their engagement and facilitating the learning process. Furthermore, it seeks to understand the specific challenges faced by these students in the school environment and how gamification can help to overcome them, thus promoting a more inclusive and effective education.